Quantitative Susceptibility Mapping: MRI at 7T versus 3T. Issue 1 (18th October 2019) - Spincemaille, Pascal; Anderson, Julie; Wu, Gaohong; Yang, Baolian; Fung, Maggie; Li, Ke; Li, Shaojun; Kovanlikaya, Ilhami; Gupta, Ajay; Kelley, Douglas; Benhamo, Nissim; Wang, Yi
ABSTRACT: BACKGROUND AND PURPOSE: Ultrahigh‐field 7T promises more than doubling the signal‐to‐noise ratio (SNR) of 3T for magnetic resonance imaging (MRI), particularly for MRI of magnetic susceptibility effects induced by B 0 . Quantitative susceptibility mapping (QSM) is based on deconvolving the induced phase (or field) and would therefore benefit substantially from 7T. The purpose of this work was to compare QSM performance at 7T versus 3T in an intrascanner test‐retest experiment with varying echo numbers (5 and 10 echoes). METHODS: A prospective study in N = 10 healthy subjects was carried out at both 3T and 7T field strengths. Gradient echo data using 5 and 10 echoes were acquired twice in each subject. Test‐retest reproducibility was assessed using Bland‐Altman and regression analysis of region of interest measurements. Image quality was scored by an experienced neuroradiologist. RESULTS: Intrascanner bias was below 3.6 parts‐per‐billion (ppb) with correlation R 2 > .85. Interscanner bias was below 10.9 ppb with correlation R 2 > .8. The image quality score for the 3T 10 echo protocol was not different from the 7T 5 echo protocol ( P = .65). CONCLUSION: Excellent image quality and good reproducibility was observed. 7T allows equivalent image quality of 3T in half of the scan time.